A retenção de talentos no varejo bancário - Almeida, César Rodrigues de (2009)
This work aims to recognize and demonstrate through the expectations and wishes of the new banking employee what they think about the future of labor market. How to plan their careers, their image for the bank firm and what is more important in their ambition to stay or leave the institution. Bank industry should improve its relationship with their customers, as a matter of fact there is an increase even in concentration and competition by the institutions. More over, banks should empower and transform their employees into customer relationship agents. With technological changes and the transformation, in the last decade, of the labor market characteristic, financial firms are facing a greater competition from other careers, so that their talents are disputed by other segments. In this new reality of greater concentration, intense competition, greater demands from customers and careers competition banks have been given a high turnover in their early careers. What hinders the improvement of their career. We made use of participant observation with active participation in the community studied, making use of field notes, as well as conducting informal interviews and focused. In this context the research were focuses in employees with a maximum of 5 years of banking work in a large financial institution, which are at the initial positions of the banking career in public services agencies of the Sao Paulo city and specializing on serving the public universities. The main result of this study is that all banking employees have already received offers to switch jobs, in their short careers. In other words, banking employees are harassed by other corporate companies. Thus, in the case of an improvement in the Brazilian labor market, the bank industry will have difficult to retain their talents. In our research it became clear that today when banking employees are invited for another job and do not accept, it depends on the opportunities offers by the bank, on the vision of the future and greatly the image and brand of the institution. The banking employees knows the thru value of their salary and will only be seduced by a good pay offer, if it comes with benefits and the image of the new company should be at least the same of the bank where the employee works. Nowadays, a good pay offer should come together with a career plan. The research focus on workers up to 29 years old whom are at the moment of future decisions, for them is not enough just having a good financial offer or benefits or a good corporate image, the company must join all of this with future career s perspective